Acceptance of Health Information System for Public Health Centre in North Borneo, Indonesia - Nurul Irma Kusumawati; Sulistyawati Sulistyawati (International Journal of Public Health Science (IJPHS), 2018)
This study sought the factor associated with own acceptance of HIS for PHC by using the modification of Technology Acceptance Model (TAM) in the Sebengkok PHC, Central Tarakan Subdistrict, Tarakan City, North Borneo, Indonesia. A cross-sectional approach was conducted through a survey on the 37 of PHC’s user. A set of questionnaires which was adopted from the previous research was used to collect the information from the participant. The model was developed by involving job relevance, output quality, result demonstrability, screen design, terminology, facilitating condition, perceived of usefulness, perceived ease of use, intention to use and system use (actual usage) as the construct. According to the hypothesis testing, perceived usefulness predicted by terminology, perceived ease of use is significantly predicted by screen design and terminology, perceived usefulness significantly predicts the intention of use and perceived ease of use, while system use which predicted considerably by the intention of use and facilitating condition. This study may have a contribution to the future improvement of HIS for PHC and guide the next coming research to dig the difference acceptance among the user.